ABOUT THE WAYS OF THE SYSTEM ANALYSIS OF METAL MOVEMENT IN GATING SYSTEMS BASED ON THE NUMERICAL SOLUTIONS OF NAVIER-STOKES EQUATIONS - S. G. Lizouzov; A. N. Chichko; V. F. Sobolev; O. A. Sachek; T. V. Matyushinets; O. I. Chichko; Yu. V. Yatskevich (Литьë и металлургия)
Numerical modeling of distribution of the fields of speeds projections on axes X, Y, Z in gating system with the casting “Case of conical pair” for various temporal values is carried out. Numerical criteria for assessment of metal movement through the feeders having various spatial location relative to the gating system are offered. Dynamics of change of the offered criteria on the basis of integral average value of the speed component on axes X, Y, Z in the gating systems at the outlet from feeder is calculated.